(untitled) (Applied Biological Research, 2023)
The forensic flies colonize and feed on carcasses and cadavers and draw their nourishment from the dead and decomposed matter. They find significance in forensic studies as nutrient recyclers, disease vector and reveal association with pathogenic microorganisms. Despite their importance in forensistudies, their innate immune defense molecules like antimicrobial peptides (AMPs), have not been well characterized. Therefore, we characterized the AMPs from forensic fly, Calliphora vicina. using MSA, NCBI Tree Viewer, I-TASSER, Peptide cutter, NetPhos 3.1, Prot param Expasy insilico tools, for prediction of homology and evolutionary relationships, structure, function, potential cleavage, phosphorylation sites and physicochemical properties. We report for the first time thdifferences in the structures of C. vicina AMPs and the presence of nucleic acid-binding domain in Cecropin, at aspartic acid (D19), glutamine (Q15), histidine (H16) probably contributing to the antiviral immune responses. This in-silico study highlights the diversity of AMPs in forensic flies and reveals their indepth structural information. Further, these AMPs partially explain their association with pathogenic microorganisms.